Russian Small-Scale Bronze Sculpture in the Late 19th — Early 20th century: the Problem of Creative Method - Gangan, Andrey V. (Actual Problems of Theory and History of Art, 2025)
In the late 19th — early 20th cc. small-scale bronze sculpture underwent cardinal changes, connected with the general crisis of the form-building. The Impressionism, popular in Russian sculpture in the end of the 19th c., contributed to reconsidering the principles of form-building. Almost every advanced or young sculptor submitted to the Impressionist influence in a varying degree, however later each of them obtained his own manner.
Keywords: small-scale sculpture; Impressionism; Russian bronze; creative method